New oral anticoagulants for atrial fibrillation - Yakobus, Yuliana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Atrial fibrillation (AF) is the most common cardiac arrhythmia in the world. Four new oral anticoagulants have become available as alternatives for warfarin in patients with AF. Although the newer aspects have higher acquisition cost, the benefits of cost savings may be derived from potential for decreasing the bleeding incidence and reducing the need for anticoagulation monitoring.